Oscillation frequencies of the reinforced wall of a steel vertical cylindrical tank for petroleum products depending on winding pre-tension - Tursunkululy, Timur; Zhangabay, Nurlan; Avramov, Konstantin; Chernobryvko, Maryna; Kambarov, Medetbek; Abildabekov, Arman; Narikov, Kanat; Azatkulov, Otabek (Eastern-European Journal of Enterprise Technologies, 2023)
This paper reports a study of the frequencies and vibration modes of a vertical steel tank with a variable wall thickness in the ANSYS software suite using a finite-element model of vibrations of a tank with a volume of 3000 m3 for oil and petroleum products, hardened by a prestressed winding. The simulation was carried out for two variants of fixing the upper edge of the tank wall, which correspond to cases of absence or presence of tank coating. The estimation cases for the coefficients of the tension force of the wire relative to its tensile strength were investigated: at k1=0.2; k2=0.4; k3=0.6 and k4=0.8. Variation studies were carried out both taking into account the additional loads caused by the action of hydrostatic pressure from the maximum and half poured oil into the tank, and without oil. The magnitude of changes in the vibration frequencies of the tank wall without the influence of the coating varies within 12–27 % and when taking into account the influence of tank coating, 21–62 %, depending on the degree of filling of the tank. The revealed pattern relates to the fact that a decrease in the tension force of the filament in the winding leads to an increase in the frequency of oscillations. Thus, pre-stress can be applied to regulate the oscillation frequency of the tank wall. By decreasing which in the winding, it is possible to increase the natural frequencies of the wall and to lower the frequencies through an increase in the prestress. The research results can be used in the future as anti-seismic measures in the design and construction of steel vertical cylindrical tanks, as well as to improve the strength characteristics of existing cylindrical structures